PARAMETER DEMOGRAFI PARASITOID HEMIPTARSENUS VARICORNIS (GIRAULT) (HYMENOPTERA: EULOPHIDAE) PADA LALAT PENGOROK DAUN LIRIOMYZA HUIDOBRENSIS (DIPTERA : AGROMYZIDAE) - Sulaeha, Aunu Rauf , dan Nina Maryana . (Universitas Lampung, 2009)
Demographic parameter Parasitoid Hemiptarsenus varicornis Girault (Hymenoptera: Eulophidae) on Leafminer Liriomyza huidobrensis. Hemiptarsenus varicornis Girault (Hymenoptera: Eulophidae) is the most common parasitoid associated with larvae of potato leafminer Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) in Indonesia. The leaf miner was reared on redbean. Demographic parameters was determined by observation of 50 larvae. Daily mortality and fertility were calculated using a life table analysis. Life table analysis showed that the net reproductive rate (Ro) was 18.021 females per generation, instrinsic growth rate ( r ) was 0.208 female offspring per female per day, limited increased rate ( ë ) was 1.231 individuals per day, generation time ( T ) was 13.9 days, and total reproduction value (RVx) was 80.847 and its peak was reached when adults were three days old. Leslie matrix simulation showed proportions of parasitoid’s egg, larva, pupa, and adult. Which are 35%, 30,6%, and 18%, respectively were stabilized since 40 days after release.